Extraction of titanium nanoparticles from synthetic rutile via modified hydrothermal synthesis method with a silver doped by molten salt process - Huzaikha Awang (2018)
In this research work, Titanium Dioxide (TiO2) was synthesized from the synthetic rutile via a modified hydrothermal synthesis method and then was doped with a silver via a molten salt process. The main objectives in this research work are to find the optimum condition of high grade TiO2 extraction and the optimum condition to extract the high crystalline Silver-Titanium (Ag-TiO2). The high crystalline Ag-TiO2 was extracted to improve its application for commercialize purpose especially in enhancing the fabricated solar cell efficiency industry. Firstly, we vary the molarity of acid sulfuric, treatment time, temperature and ratio in our modified hydrothermal synthesis method to synthesize the optimum condition to extract a high grade TiO2 nanoparticles. After that, we characterize our samples using the Energy Dispersive X-ray spectroscopy (EDX), X-ray Diffraction spectroscopy (XRD), Field Emission Scanning Electron Microscope (FESEM) and High ResolutionTransmission Electron Microscopy (HRTEM). As the result, we found that, the optimum condition to extract the high grade TiO2 was occurred at 2.2M acid molarity, 4 hours treatment time, 80oC fixed temperature and 1:4 Na2TiO3:acid ratio at 600oC calcination. Secondly, we vary the molarity of silver in our molten salt process to improve the nanocrystal crystallinity of Ag-TiO2 via a doping method. We characterize our samples by using X-ray Diffraction (XRD), Surface Area BET (SBET), UV-Vis-NIR spectrophotometer (UV-Vis), Field Emission Scanning Electron Microscope (FESEM) and High Resolution Transmission Electron Microscopy (HRTEM). As the result, we found that, the optimum condition to extract the high purity and high crystallinity of Ag-TiO2 were occurred at 1% and 5% of silver molarity at 600oC calcination. Finally, we characterize the effectiveness of high crystalline Ag-TiO2 by using a Methylene Blue Degradation (MBD) at Agensi Nuklear Malaysia. We were irradiated our samples with two types of light, which are visible light and Ultra Violet (UV) light. For the visible light irradiation, the high grade TiO2 shows a 25% while the high crystalline 5% Ag-TiO2 are 66% photodegradation performance. Besides that, for the UV light irradiation, the high grade TiO2 shows a 50% while the high crystalline 5% Ag-TiO2 are 75% photodegradation performance. This analyzation proves that, the nanocrystal crystallinity of Ag-TiO2 was improved by adding the silver dopant via a molten salt doping process.